Gambaran Konsep Diri Remaja yang Mengalami Masa Pubertas di SMK Kesehatan Panca Atma Jaya Kabupaten Klungkung Tahun 2012 - Setiawan, I Made Dody; Muryani, Ni Made Sri; Achjar, Komang Ayu Henny; Febianingsih, Ni Putu Eka (Akademi Keperawatan Kesdam IX/Udayana, 2018)
ABSTRACT Background: Teen are transition age from childhood to adulthood, in adolescence age the individuals will experience a change in attitudes, behaviors in line with the level of physical growth. Teenagers are very easily influenced by factors that exist outside of him as family, environment, society, peers and school friends. When enter puberty, every child has personality system that established from development so far. The concept gives sense of continuity, integrity, and consistency in a person which is a physical representation of an individual, the central core of